Does publish or perish lead to stylish rubbish? - Kaj Storbacka (jbm - Journal of Business Market Management, 2014)
Why are we doing academic research about business-to-business marketing? This is the fundamental question that all of us who are scholars of business and related fields should ask ourselves. To me, it is obvious that we conduct research to help managers do a better job - perhaps not immediately after they have read our individual efforts, but at least over time. If my view is a valid one, it suggests a need to redefine our impact measures, towards assessing the extent to which we influence management practice.
urn:nbn:de:0114-jbm-v7i1.858
Keywords: 650